Estoque de carbono em plantações de Eucalyptus sp. implantados em campo nativo - Wink, Charlote (2009)
The soil management with emphasis in keeping soil residues on surface combined with vegetation growth may reduce carbon (C) emission to the atmosphere. The objective of this study is to measure the effects of the Eucaliptus Forest 20, 44 and 240 months old and native grassland on carbon sequestration in Paleudult, in Santa Maria, RS. The forest production was determined by Smalian method measuring selected trees, chosen from forest inventory based on standard deviation of breast height. The carbon of trees biomass was measured by weighting dry matter of leaves, branches, wood and cork and after converting to C by multiplying by 0.45. The C content in the forest litter, grassland, soil particulate and mineral associated organic matter in six soil layers were determined by CHNS auto analyzer. Soil physical properties as total, macro and microporosity, particle density and size distribution were determined and related to Eucaliptus and grassland. Soil samples were also used to measure some soil chemical properties. The dataset were tested to detect if there were normal distribution and variance homogeneity. To normal or transformed data, analysis of Variance and Tukey test (5%) for variables with significant F was applied. The greatest C stocks were in the wood and cork in all forest ages, however, the proportinal C in leaves and branches decreased with Eucalyptus age.The C stock in forest production added to grassland and litter dry matter increased with substitution of grassland by Eucalyptus Forest, and the difference increased with the age of trees. The content and stock of soil C are low and did not increase with introduction of forest on grassland soil. The soil layers with higher clay content had less C as compared to surface layers with lower clay content and higher C. The particulate organic matter varied the most with forest age and grassland indicating higher sensibility than organic matter associated with soil minerals. The introduction of forest on grassland did not change soil physical properties suggesting that more detailed studies should be done in order to better measure the impact of trees plantation.